L’innovation et les marchés financiers aux États-Unis depuis les années 1970 : une approche contrastée - Christine Zumello (Revue LISA)
It seems particularly relevant to talk about financial innovation in the United States because this country can be considered as a major engine of innovation given the size of the financial markets and the wide variety of financial products available. Financial innovation is analysed through the lens of a genetic mutation which turns an existing financial product into a mutant under certain conditions [Merton Miller's 'seed beneath the snow']. The conditions which favour financial innovation as well as the role of regulation are considered in this paper. An insight into the potential negative market spin that can spring from financial innovation is also offered.